Laparoscopic access to the liver and application of laparoscopic microwave ablation in 2 dogs with liver neoplasia. (21st January 2019) - Oramas, Alberto; Case, J. Brad; Toskich, Beau B.; Fox‐Alvarez, W. Alexander; Boston, Sarah E.; Giglio, Robson F.; Dark, Michael J.
Abstract: Objective: To determine laparoscopic accessibility of liver lobes and access to the hilus and describe laparoscopic microwave ablation (LMWA) in 2 dogs with hepatic neoplasia. Study design: Experimental/descriptive case series. Sample population: Six canine cadavers and 2 clinical dogs. Methods: Cadavers in dorsal recumbency underwent laparoscopic assessment of the liver. A 17 gauge MWA probe was inserted to create an ablation zone at the most proximal aspect of the hilus. The distance from the center of each ablation zone to the most proximal aspect of the corresponding hilus was determined. Two dogs with hepatic neoplasia underwent LMWA. Results: All lobes of the canine liver were accessible via laparoscopy. The median (interquartile range) distances from the ablation zones to the hilus for the caudate process, left lateral, left middle, quadrate, right lateral, and right middle lobes were 2.2 (1.2–2.6), 2.1 (1–4.4), 1.5 (1.4–3.7), 2, 1, 2.5 (1–4.1) cm, respectively. Histopathologic diagnoses treated by LMWA included metastatic hemangiosarcoma and primary hepatocellular carcinoma. Laparoscopic microwave ablation was technically feasible, and no complications from the procedure resulted. Conclusion: Laparoscopic access to the hilus of each liver lobe is possible via a ventrodorsal approach provided reverse Trendelenburg and lateral rotation is used, especially for the right lateral lobe. Laparoscopic microwave ablation is feasible in some dogs with hepatic neoplasia. The indications for and efficacy of LMWA for hepatic neoplasia in dogs requires additional investigation. Clinical significance: Laparoscopic access to all liver lobes and MWA of some neoplastic lesions is feasible in a canine pilot study.